Introduction of HER-2 and a Short Review on Its Role in Prognosis and Treatment of Breast Cancer: - Mirmalek, Seyed Abbas; Elhamkani, Fatemeh; Salimi Tabatabaee, Seyed Alireza; Mahmoodzadeh, Hossein; Parsa, Yekta; Yadollah-Damavandi, Soheila; Jangholi, Ehsan (Galen Medical Journal, 2014)
Human Epidermal growth factor Receptor-2 (HER-2) as a new prognostic and predictive factor has been believed as an essential measurement in breast carcinoma. About 280 articles were reviewed and 115 were referred in this review article on HER-2. HER-2 is an oncoprotein epidermal growth factor receptor produced by a so-called cell surface oncogene. Overexpression results in aggressive behavior, early metastasis to lymph nodes and distant areas, and poor prognosis in breast cancer. HER-2 seems to be a prognostic and predictive factor and must be considered in all breast cancer cases.